2007
DOI: 10.1002/cpp.537
|View full text |Cite
|
Sign up to set email alerts
|

Paranoid beliefs and self‐criticism in students

Abstract: Paranoid beliefs are associated with negative and malevolent views of others. This study, however, explored hostile and compassionate self-to-self relating in regard to paranoid beliefs. A total of 131 students were given a series of scales measuring paranoid ideation, forms and functions of self-criticism, self-reassurance, selfcompassion and depression. Test scores were subjected to correlation and hierarchical regression analyses to explore the relative contribution of study variables to paranoid beliefs.In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 26 publications
10
68
0
1
Order By: Relevance
“…Additionally, previous research has found associations between shame, self-criticism, and paranoid ideation (e.g. Matos, Pinto-Gouveia, & Gilbert, 2013;Mills, Gilbert, Bellew, McEwan, & Gale, 2007) and, in samples of people with psychosis, shame was found to be a mediator between paranoia and social safeness .…”
Section: Fears Of Compassion (Referred As Foc Hereinafter) and Its Rementioning
confidence: 81%
“…Additionally, previous research has found associations between shame, self-criticism, and paranoid ideation (e.g. Matos, Pinto-Gouveia, & Gilbert, 2013;Mills, Gilbert, Bellew, McEwan, & Gale, 2007) and, in samples of people with psychosis, shame was found to be a mediator between paranoia and social safeness .…”
Section: Fears Of Compassion (Referred As Foc Hereinafter) and Its Rementioning
confidence: 81%
“…using bipolar constructs: kindness vs self-judgement; mindfulness vs self-absorption/over identification, and common humanity vs isolation. Low scores, indicating low self-compassion, are highly correlated with experiences of paranoia, shame and self-criticism [88]; post traumatic stress disorder [60]; depression [95] and mental health problems in general [15,83,97].…”
Section: Self-compassionmentioning
confidence: 99%
“…Research has found that higher self-compassion is positively associated with happiness, wisdom, personal initiative, curiosity, optimism, positive affect , social relationship, emotional intelligence, self-determination, life satisfaction (Neff, 2003a), and better emotional coping skills (Neff, Hseih, & Dejitthirat, 2005). On the other hand self-compassion is negatively associated with self-rumination, anger (Neff & Vonk, 2009), negative affect , depression (Mills, Gilbert, Bellew, McEwan, & Gale, 2007), submissive behaviour (Akın, 2009), loneliness (Akın, 2010), and automatic thoughts (Akın, 2012).…”
Section: Self-compassionmentioning
confidence: 99%